Peran Mustahiqah dalam Membina Akhlak Siswi Madrasah Ibtidaiyah Pesantren - Hamidah, Uswatun; Yuanita, Dianis Izzatul (Kartika: Jurnal Studi Keislaman, 2022)
This study aims to describe the role of mustahiqah in fostering student morals. The research method used in this study is qualitative, with a descriptive case study approach. Methods of data collection using observation techniques, interviews, and documentation. The informants of this study were madrasah leaders, mustahiqah, and students of Madrasah Pesantren. The results of this study concluded that: (1) The role of mustahiqah in moral development for female students is quite good by applying exemplary methods, habituation, advice, stories, and supervision to female students. (2) Mustahiqah must have good teacher competencies: personality, pedagogic, social, and professional competencies. (3) The morals of female students can be categorized as good. That is supported by supporting factors for fostering student morals: facilities, educators, learning methods, and students willing to receive lessons and advice. While the inhibiting factors are the reality of students who find it difficult to receive advice, heterogeneity, and the development of information and technology advances in the modernization era.